The Impact of Organizational Climate on Technostress and Job Satisfaction of Millennial Employee: Evidence from Indonesia - Rebi Fara Handika; Velia Meidilisa (AMAR (Andalas Management Review), 2022)
The investigation regarding the impact of organizational climate and Technostress on the millennial employee as the most prominent cohort is still rarely found in the context of developing countries, especially in Indonesia. Thus, this research aimed to test the effect of organizational climate on job satisfaction and Technostress and further examine the impact of Technostress on the job satisfaction of millennial employees in Indonesia. A web-based survey of 100 millennial workers from diverse companies in Indonesia was conducted. The data was analyzed using Partial Least Squares - Structural Equation Modeling (PLS- SEM). The results imply that a good Organizational Climate improves millennial employees’ Job Satisfaction and reduces their Technostress; meanwhile, no significant effect was found on the relationship between Technostress and Job Satisfaction. The implication and conclusion are discussed further.